2014
DOI: 10.3923/pjbs.2014.689.695
|View full text |Cite
|
Sign up to set email alerts
|

Reference Values of Six-limb-lead Electrocardiogram in Conscious Labrador Retriever Dogs

Abstract: Breed-wise standard electrocardiographic values in dogs have been reported as there is variation in body and chest conformation, which limits the application of data of one breed for other breed. Labrador retrievers being originated from hunting dogs, their electrocardiogram (ECG) values might be different from standard normal range of other dog breeds. So, the purpose of the present study was to determine the standard ECG of Labrador retrievers and to check effect of body weight, gender and breed upon differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
39
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(64 citation statements)
references
References 5 publications
23
39
0
2
Order By: Relevance
“…3,8,10,16,17 Ejection fraction and fractional shortening were not correlated with bodyweight in this study, which is in agreement with Bonagura, 3 Lombard, 16 and Crippa et al, 6 who reported a lack of correlation between body size and cardiac function indices like FS and EF. The lack of dependence of these indices on body size would tend to suggest a high level of cardiac functional homogeneity in the breed studied.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…3,8,10,16,17 Ejection fraction and fractional shortening were not correlated with bodyweight in this study, which is in agreement with Bonagura, 3 Lombard, 16 and Crippa et al, 6 who reported a lack of correlation between body size and cardiac function indices like FS and EF. The lack of dependence of these indices on body size would tend to suggest a high level of cardiac functional homogeneity in the breed studied.…”
Section: Discussionsupporting
confidence: 89%
“…17,8 The indexed EDV and ESV values obtained in this study were respectively less than 100 mL/m 2 and 30 mL/m 2 and could be described as normal. 18 In spite of the relatively smaller size of the Nigerian local dog this study showed that its mean and median EDV and ESV were still respectively higher and lower than those of other outdoor dogs such as the Hungarian breed of dogs.…”
Section: Discussionmentioning
confidence: 52%
“…In dogs, cardiac arrhythmias and intra-cardiac conduction disturbances are commonplace problems, which can be well elucidated using ECG [ 5 ]. But in India, the exotic breeds are extensively used to perform sniffing activities by different security agencies and also reared in pet lovers’ den.…”
Section: Introductionmentioning
confidence: 99%
“…So, the VHS method could help in the interpretation of the ECG of dogs with different thoracic conformations. The scientific literature presents the ECG [12,18,24] and VHS [7,8] values in dog of different breeds and sizes; however, there is little information about the correlation of these parameters in healthy dogs.…”
Section: Introductionmentioning
confidence: 99%